Solution thermodynamics and its application to aqueous solutions a differential approach - Koga, Yoshikata (Amsterdam Elsevier Science, 2017)
Solution Thermodynamics and its Application to Aqueous Solutions: A Differential Approach, Second Edition introduces a differential approach to solution thermodynamics, applying it to the study of aqueous solutions. This valuable approach reveals the molecular processes in solutions in greater depth than that gained by spectroscopic and other methods. The book clarifies what a hydrophobe, or a hydrophile, and in turn, an amphiphile, does to H2O. By applying the same methodology to ions that have been ranked by the Hofmeister series, the author shows that the kosmotropes are either hydrophobes or hydration centers, and that chaotropes are hydrophiles. This unique approach and important updates make the new edition a must-have reference for those active in solution chemistry.--Provided by publisher.
Includes bibliographical references and index.
Electronic reproduction.
Keywords: Solution (Chemistry); Thermodynamics; Electronic books